2021
DOI: 10.3390/molecules26227056
|View full text |Cite
|
Sign up to set email alerts
|

Isoorientin Inhibits Amyloid β25–35-Induced Neuronal Inflammation in BV2 Cells by Blocking the NF-κB Signaling Pathway

Abstract: Alzheimer’s disease (AD) is a severe neurodegenerative disorder. AD is pathologically characterized by the formation of intracellular neurofibrillary tangles, and extracellular amyloid plaques which were comprised of amyloid-beta (Aβ) peptides. Aβ induces neurodegeneration by activating microglia, which triggers neurotoxicity by releasing various inflammatory mediators and reactive oxygen species (ROS). Nuclear factor-kappa B (NF-κB) is expressed in human tissues including the brain and plays an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The fact that the results were observed in brain immune response cells (microglia), which can increase β-amyloid (Aβ) phagocytosis in a PPAR-γ-dependent manner, 56 indicates a potential neuroprotective effect of PS metabolites. The findings by Kim et al 55 also demonstrate the neuroprotective effect of isoorientin on BV-2 cells. The results corroborate the findings of the nutrigenomic analysis carried out by Duarte et al , 18 which revealed the negative modulation of more than 1300 genes involved in inflammation, the cytokine–cytokine receptor, and the cell adhesion processes after PS consumption, in addition to the reduced levels of insulin, HOMA-IR and IL-17A in the participants.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The fact that the results were observed in brain immune response cells (microglia), which can increase β-amyloid (Aβ) phagocytosis in a PPAR-γ-dependent manner, 56 indicates a potential neuroprotective effect of PS metabolites. The findings by Kim et al 55 also demonstrate the neuroprotective effect of isoorientin on BV-2 cells. The results corroborate the findings of the nutrigenomic analysis carried out by Duarte et al , 18 which revealed the negative modulation of more than 1300 genes involved in inflammation, the cytokine–cytokine receptor, and the cell adhesion processes after PS consumption, in addition to the reduced levels of insulin, HOMA-IR and IL-17A in the participants.…”
Section: Discussionmentioning
confidence: 74%
“…It was not possible to identify changes in the expression of p50 and p65, the NF-κB subunits, in vitro . Although this transcription factor is directly related to PS-modulated genes as suggested in Duarte et al 18 and in the recent study by Kim et al , 55 isoorientin, a flavonoid present in PS, was able to inhibit the activation of NF-κB in BV-2. Perhaps a greater stressor stimulus than the one used in this study was necessary to be able to identify the statistical differences.…”
Section: Discussionmentioning
confidence: 83%
“…32,38,39 Previous research on amyloid peptides has shown a similar trend, with an increase in M1 markers and a decrease in M2 markers, contributing to microglial polarization. 36,40,41 Similarly, studies on heavy metals have yielded analogous results, suggesting a shift toward the neurotoxic M1 state based on the variations in M1 and M2 marker expression. 34,42,43 Our findings unveiled that Pb and amyloid peptides play a crucial role in pathophysiological processes that culminate in neurodegeneration by possibly inducing M1 polarization, as clearly indicated by the substantial elevation in the levels of M1 polarization markers.…”
Section: Discussionmentioning
confidence: 79%
“…Previous in vitro experiment results indicated that gentiopicroside (2) inhibited NO, IL-6, and PGE2 in LPS-activated RAW 264.7 cells [25,49]. Loganic acid (3), isoorientin (4), and isovitexin (5) were also reported to possess anti-inflammatory activity [25,[50][51][52]. Loganic acid (3) exhibited in vivo antiinflammatory effect by reducing TNF-α and IL-6 activity [53].…”
Section: Analgesic Activitymentioning
confidence: 99%